Pelaksanaan Program Dirasah Islamiyah sebagai Upaya Peningkatan Kualitas SDM Masyarakat di Desa Sicini - Chamdar Nur (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
One form of community service conducted by STIBA Makassar Community Service Program (KKN) students in Sicini Village, Parigi District, Gowa Regency, was implementation of Islamic education programs (Dirasah Islamiyah). The objective of this program was to enhance Islamic comprehension and competence of people in Sicini. The details of the Islamic learning program consisted of: (1) Presenting Islamic teacing in schools; (2) Basic teaching of Koran at TKA/TPA; (3) Tajwid learning; (4) Dirosa teaching; (5) Training for funeral; and (6) Tabligh Akbar. Outputs of the programs is a positive contribution in improving the comprehension and competence of human resources in muslim community in Sicini Village.